2021
DOI: 10.25282/ted.757823
|View full text |Cite
|
Sign up to set email alerts
|

Tıp eğitimi sırasında Türk tıp öğrencilerinin uzmanlık tercihlerinde değişiklik

Abstract: Tıp eğitimi sırasında Türk tıp öğrencilerinin uzmanlık tercihlerinde değişiklik Change in choices regarding the residency of Turkish medical students during medical education Özet Arka Plan: Tıp öğrencilerinin seçimleri, ahlaki değerlerine ve gelecekteki mesleklerinden beklentilerine bağlıdır. Bu seçim kişisel olsa da sağlık sistemi üzerinde etkileri vardır. Türkiye'de doktorların uzmanlık alanına göre yanlış dağılımı önemli bir sorun ve sağlık sunum sisteminin sürdürülebilirliği için bir risk haline gelmiştir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The specialization trends from 1987 to 2017 showed that it could create serious problems for sustainable healthcare services in Turkey because some specialties are strongly demanded by students while some specialties cannot fill even half of their available positions [ 15 , 16 ]. One of the prominent reasons stated by Turkish students avoiding certain specialties is, similar to our results, poor working conditions in these specialties [ 17 ]. Similarly, the specialization trend is a serious problem in Spain, especially for primary care [ 18 ].…”
Section: Discussionsupporting
confidence: 87%
“…The specialization trends from 1987 to 2017 showed that it could create serious problems for sustainable healthcare services in Turkey because some specialties are strongly demanded by students while some specialties cannot fill even half of their available positions [ 15 , 16 ]. One of the prominent reasons stated by Turkish students avoiding certain specialties is, similar to our results, poor working conditions in these specialties [ 17 ]. Similarly, the specialization trend is a serious problem in Spain, especially for primary care [ 18 ].…”
Section: Discussionsupporting
confidence: 87%
“…While changing residency option is not unusual during medical studies [14,15], we aimed to assess whether medical students were keener to do so after migrating to online education during lockdown. A further mixed-methods study could analyze whether there are relevant data to corelate the perceived quality of medical education to the desire to change residency choice.…”
Section: Resultsmentioning
confidence: 99%
“…The COVID-19 pandemic, according to all current estimates, will continue and will develop new facets in affecting the mental status of the general population, health workers, and medical students [10,13,15]. Medical education, like many other areas that involve direct engagement with the beneficiary, or patient, will have to adapt to the new circumstances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation